4D flow MRI-based computational analysis of blood flow in patient-specific aortic dissection - Pirola,S; Guo,B; Menichini,C; Saitta,S; Fu,W; Dong,Z; Xu,XY (IEEE Transactions on Biomedical Engineering, 2019)
OBJECTIVE: Computational hemodynamics studies of aortic dissections usually combine patient-specific geometries with idealized or generic boundary conditions. In this study we present a comprehensive methodology for simulations of hemodynamics in type B aortic dissection (TBAD) based on fully patient-specific BCs. METHODS: Pre-operative 4D flow magnetic resonance imaging (MRI) and Doppler-wire pressure measurements (pre- and post-operative) were acquired from a TBAD patient. These data were used to derive boundary conditions for computational modelling of flow before and after thoracic endovascular repair (TEVAR). Validations of the computational results were performed by comparing predicted flow patterns with pre-TEVAR 4D flow MRI, as well as pressures with in vivo measurements. RESULTS AND CONCLUSION: Comparison of instantaneous velocity streamlines showed a good qualitative agreement with 4D flow MRI. Quantitative comparison of predicted pressures with pressure measurements revealed a maximum difference of 11 mmHg (-9.7%). Furthermore, our model correctly predicted the reduction of true lumen pressure from 74/115 mmHg pre-TEVAR to 64/107 mmHg post-TEVAR (diastolic/systolic pressures at entry tear level), compared to the corresponding measurements of 72/118 mmHg and 64/114 mmHg. This demonstrates that pre-TEVAR 4D flow MRI can be used to tune boundary conditions for post-TEVAR hemodynamic analyses.